Populism and the politicisation of foreign policy. (August 2022) - Destradi, Sandra; Plagemann, Johannes; Taş, Hakkı
Populists in power often resort to the politicisation of foreign policy to generate domestic support. This article explores this process. First, it conceptualises populist politicisation of foreign policy. Second, it develops expectations on how such politicisation will take place: the distinctive features of populism (the intensity of populist discourse, the relative weight of anti-elitism and people-centrism, and a transnational understanding of the 'people' or the 'elite') will have an impact on how foreign policy is politicised. The empirical analysis focuses on selected public speeches and tweets by two populist leaders from the Global South: Recep Tayyip Erdoğan and Narendra Modi. The analysis reveals huge differences: the more populist Erdoğan emphasises anti-elitism and extensively resorts to the politicisation of Turkish foreign policy by constructing foreign threats. Modi is less populist and his discourse emphasises people-centrism; as expected, he only marginally politicises foreign policy, highlighting the greatness of the Indian nation.